2014
DOI: 10.1093/brain/awu036
|View full text |Cite
|
Sign up to set email alerts
|

Mild cognitive impairment is linked with faster rate of cortical thinning in patients with Parkinson’s disease longitudinally

Abstract: Previous studies have shown greater atrophy in grey and white matter of various brain regions in patients with Parkinson's disease with mild cognitive impairment than in those without. These anatomical differences likely account for the distinct clinical profiles observed between those groups, but do not account for the evolution of regional brain degradation observed as the disease evolves. Although we have shown recently that cortical thinning correlates significantly more with disease duration in Parkinson'… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

20
169
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 185 publications
(199 citation statements)
references
References 74 publications
20
169
1
Order By: Relevance
“…Voxel-based morphometry (VBM) of gray matter and hippocampus by 1.5T volumetric MRI was included because significant atrophy has been described in correlation with PD progression and cognitive decline. 15 We also investigated serum urate. 16 We tested known CSF markers that have been previously discussed as potential diagnostic markers of PD state or its progression, including total a-synuclein (a-syn), b-amyloid 1-42, total and phosphorylated tau protein (t-tau and p-tau), as well as neurofilament light chain proteins.…”
mentioning
confidence: 99%
“…Voxel-based morphometry (VBM) of gray matter and hippocampus by 1.5T volumetric MRI was included because significant atrophy has been described in correlation with PD progression and cognitive decline. 15 We also investigated serum urate. 16 We tested known CSF markers that have been previously discussed as potential diagnostic markers of PD state or its progression, including total a-synuclein (a-syn), b-amyloid 1-42, total and phosphorylated tau protein (t-tau and p-tau), as well as neurofilament light chain proteins.…”
mentioning
confidence: 99%
“…95,96 Longitudinal studies of patients with PD-MCI have shown that these areas progressively lose volume and this correlates with cognitive deficit. 95,97 By the time PDD is diagnosed, there is significant thinning of the parietal, occipital, frontal and temporal regions, plus further atrophy of the hippocampus, parahippocampus, insular and cingulate. 98,99 Diffusion tensor imaging (DTI) has revealed evidence of reduced structural connectivity in similar regions -in …”
Section: Biomarkersmentioning
confidence: 99%
“…[7][8][9][10] More recently, research revealed that deep GM atrophy specifically plays an important role in the characterization, course, and progression of AD [11][12][13][14][15][16][17] and in other diseases like MS [18][19][20] and Parkinson disease. [21][22][23] Measurements of deep GM atrophy could therefore be of importance in the evaluation of neuroprotective treatment (eg, in investigating drug efficacy). Currently, a growing number of clinical trials are incorporating brain volume changes as an early biomarker.…”
mentioning
confidence: 99%